An Updated Checklist of the Orchidaceae of Honduras - Vega, Hermes; Cetzal-Ix, William; Mó, Edgar; Romero-Soler, Katya J.; Basu, Saikat K. (Phytotaxa, 2022)
A comprehensive compilation of all currently recognized orchid species known from Honduras is presented. The checklist includes 604 taxa in 145 genera; 595 species, two subspecies and seven natural hybrids. Orchidaceae represents 7% of the flora of country and continues to be the plant family with the highest number of species in Honduras. The most species rich genera in the country are Epidendrum (76 species), Lepanthes (28), Stelis (26), Prosthechea (21), Habenaria (19), and Malaxis (17). Regarding the habit, 74% of the taxa are epiphytes, 20% are terrestrial, 1.5% are hemiepiphytes, 1.5% are lithophytes and 3% can be terrestrial and epiphytic. Most of the botanical collections in Honduras were made by foreign researchers between the 1920s and 1970s. Among the orchid specimens available for the current study, 44% were deposited in national herbaria and 46% in herbaria in the United States of America. The departments with more than 100 voucher specimens each are Atlántida, Comayagua, Cortés, Francisco Morazán, Lempira, and Santa Bárbara. Only 7% of Protected Natural Areas have more than 121 voucher specimens, 70% has less than 120 specimens, and remaining 23% have no available records at all. In some cases they have poor accessibility and inadequate road infrastructure. Honduras has 10 endemic orchid species, three distributed in the Mosquito province, four in the Chiapas Highlands province, and three shared by both provinces. The number of orchid taxa known to occur in Honduras may continue to increase as additional collection efforts are made. This further helps to fill in the knowledge gaps on the distribution patterns of orchids and other plant groups in Central America.